2022
DOI: 10.3389/fphar.2022.950831
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analyses identify DCBLD2 as an oncogenic, immunological, and prognostic biomarker

Abstract: Discoidin, CUB, and LCCL domain-containing protein 2 (DCBLD2) is a two-domain transmembrane protein-coding gene located on chromosome 3, the protein expressed by which acts as the membrane receptor of semaphorin and vascular endothelial growth factor during the development of axons and blood vessels. Although several research evidences at the cellular and clinical levels have associated DCBLD2 with tumorigenesis, nothing is known regarding this gene from a pan-cancer standpoint. In this study, we systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Transcriptional annotation of S2 correlated evidence of relative upregulation of gene sets affiliated with KRAS signaling (IC = 0.75, p = 0.001); protein expression and mutational data (i.e., KRAS ), however, did not consistently demonstrate perturbations correlated with commonly dysregulated components in these pathways, suggesting that parallel transcriptional events might underlie the upregulation of this oncogenic network (Figure 1). Identification of common genes in pro‐tumorigenic pathways most highly correlated with State 2 (e.g., KRAS and Rb ) elucidated a series of genes empirically associated with invasiveness and metastasis, including inhibin A 23 (IC = 0.70, p < 0.001), ETS1 24 (IC = 0.68, p < 0.001), and DCBLD2 25 (IC = 0.62, p < 0.001). Additional gene expression sets corresponding to cellular motility (IC = 0.66, p < 0.001) and an invasive phenotype (i.e., TGF‐β signaling [IC = 0.64, p < 0.001]) were also fairly well correlated with State 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional annotation of S2 correlated evidence of relative upregulation of gene sets affiliated with KRAS signaling (IC = 0.75, p = 0.001); protein expression and mutational data (i.e., KRAS ), however, did not consistently demonstrate perturbations correlated with commonly dysregulated components in these pathways, suggesting that parallel transcriptional events might underlie the upregulation of this oncogenic network (Figure 1). Identification of common genes in pro‐tumorigenic pathways most highly correlated with State 2 (e.g., KRAS and Rb ) elucidated a series of genes empirically associated with invasiveness and metastasis, including inhibin A 23 (IC = 0.70, p < 0.001), ETS1 24 (IC = 0.68, p < 0.001), and DCBLD2 25 (IC = 0.62, p < 0.001). Additional gene expression sets corresponding to cellular motility (IC = 0.66, p < 0.001) and an invasive phenotype (i.e., TGF‐β signaling [IC = 0.64, p < 0.001]) were also fairly well correlated with State 2.…”
Section: Resultsmentioning
confidence: 99%
“…(IC = 0.70, p < 0.001), ETS124 (IC = 0.68, p < 0.001), and DCBLD225 (IC = 0.62, p < 0.001). Additional gene expression sets corresponding to cellular motility (IC = 0.66, p < 0.001) and an invasive phenotype (i.e., TGF-β signaling [IC = 0.64, p < 0.001]) were also fairly well correlated with State 2.…”
mentioning
confidence: 99%
“…DCBLD2 has been revealed to be overexpressed in CRC tissues, and the overexpression of DCBLD2 links with a higher AJCC grade, a higher vascular invasion incidence, a poorer histological differentiation degree, as well as a poorer overall survival in CRC patients 43 . DCBLD2 might be a potential immunological, oncogenic, as well as prognostic hallmark in terms of pan‐cancer, which could contribute to the tumor prognosis improvement and the targeted therapy development 44 …”
Section: Discussionmentioning
confidence: 99%
“…As DCBLD2 is known to be involved in vascular damage repair (22), it is possible that plasma DCBLD2 levels in RP are elevated secondary to tissue damage and that lower levels of DCBLD2 in patients with ultra-rare damaging variants may render certain tissues, such as cartilage, more prone to inflammatory insult. A recent analysis revealed that upregulation of DCBLD2 is associated with tumor immunosuppression across multiple cancer types (30).…”
Section: Discussionmentioning
confidence: 99%